Arming the Outlaws: On the Moral Limits of the Arms Trade. (February 2019) - Christensen, James
There is a general presumption against arming outlaw states. But can that presumption sometimes be overturned? The argument considered here maintains that outlaw states can have legitimate security interests and that transferring weapons to these states can be an appropriate way of promoting those interests. Weapons enable governments to engage in wrongful oppression and aggression, but they also enable them to fend off predators in a manner that can be beneficial to their citizens. It clearly does not follow from the fact that a state is oppressive or aggressive that it will never be a victim of wrongful aggression itself, and while an outlaw state's primary aim in repelling such aggression will often be the preservation of its own power, its defensive manoeuvres will sometimes also serve its citizens' interests. In short, supplying weapons to outlaw states may sometimes contribute to the protection of innocents.